Unbundling curbside parking costs from housing prices. (13th February 2018) - Bakis, Ozan; Inci, Eren; Senturk, Rifat Ozan
Abstract: This article empirically shows that at least some of the costs of curbside parking spaces are capitalized in housing prices even though these parking spaces are not formally bundled with housing units. Making use of Istanbul's transition from free and informal curbside parking to paid and formal, we find that housing prices decreased substantially in response to city operated curbside parking, whereas rents remained statistically the same or, at best, decreased only very slightly.